2006
DOI: 10.1182/blood-2006-07-037077
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression signature of benign monoclonal gammopathy evident in multiple myeloma is linked to good prognosis

Abstract: Monoclonal gammopathy of undetermined significance (MGUS) can progress to multiple myeloma (MM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
288
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(304 citation statements)
references
References 30 publications
15
288
0
1
Order By: Relevance
“…Overexpression of MMSET was found in glioblastoma compared to normal brain (P = 1.7E-14, P = .009, P = .002) [11; 12; 13]; in hepatocellular carcinoma compared to normal liver (P = 2.9E-7, 1.3E-6) [14; 15]; in head and neck cancer compared to the normal (P = .008, P = 2.7E-5) [16; 17]; in bladder carcinoma compared to normal bladder (P = 4.1E-11, P = 1.8E-7) [18; 19]; in primary colon cancer compared to normal adjacent mucosa (P = 9.5E-6) [20]; in esophagus adenocarcinoma compared to normal esophagus (P = .004) [21]; in breast carcinoma compared to normal breast (P = 3.8E-8) [22]; in T-cell acute lymphoblastic leukemia compared to normal bone marrow (P = 5.1E-7) [23]; in B-cell acute lymphoblastic leukaemia compared to normal bone marrow (P = .001) [23]; in lung adenocarcinoma compared to normal lung (P = .009, P = 8.4E-4, 1.7E-6) [24; 25; 26]; in lymphoma compared to normal B-cell (P = 3.5E-5, 7.3E-5) [27]; in cutaneous melanoma compared to normal melanocyte ( P = 6.46E-13, P = .01, P =.009) [28; 29; 30]; in smoldering multiple myeloma compared to normal bone marrow (P = 7.3E-4) [31]; in prostate cancer compared to normal prostate (P = 1.8E-6, P = .039, P = 5.1E-8, P = .002, P = .009, P = .006, P = .009) [32; 33; 34; 35; 36; 37; 38]; in yolk sac tumor compared to normal testis (P = .003) [39]; in ovarian carcinoma compared to normal ovary (P = .002, P = 1.1E-4) [40; 41] and in clear cell carcinoma compared to normal kidney tissue (P = .006) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of MMSET was found in glioblastoma compared to normal brain (P = 1.7E-14, P = .009, P = .002) [11; 12; 13]; in hepatocellular carcinoma compared to normal liver (P = 2.9E-7, 1.3E-6) [14; 15]; in head and neck cancer compared to the normal (P = .008, P = 2.7E-5) [16; 17]; in bladder carcinoma compared to normal bladder (P = 4.1E-11, P = 1.8E-7) [18; 19]; in primary colon cancer compared to normal adjacent mucosa (P = 9.5E-6) [20]; in esophagus adenocarcinoma compared to normal esophagus (P = .004) [21]; in breast carcinoma compared to normal breast (P = 3.8E-8) [22]; in T-cell acute lymphoblastic leukemia compared to normal bone marrow (P = 5.1E-7) [23]; in B-cell acute lymphoblastic leukaemia compared to normal bone marrow (P = .001) [23]; in lung adenocarcinoma compared to normal lung (P = .009, P = 8.4E-4, 1.7E-6) [24; 25; 26]; in lymphoma compared to normal B-cell (P = 3.5E-5, 7.3E-5) [27]; in cutaneous melanoma compared to normal melanocyte ( P = 6.46E-13, P = .01, P =.009) [28; 29; 30]; in smoldering multiple myeloma compared to normal bone marrow (P = 7.3E-4) [31]; in prostate cancer compared to normal prostate (P = 1.8E-6, P = .039, P = 5.1E-8, P = .002, P = .009, P = .006, P = .009) [32; 33; 34; 35; 36; 37; 38]; in yolk sac tumor compared to normal testis (P = .003) [39]; in ovarian carcinoma compared to normal ovary (P = .002, P = 1.1E-4) [40; 41] and in clear cell carcinoma compared to normal kidney tissue (P = .006) [42].…”
Section: Resultsmentioning
confidence: 99%
“…This unbalanced expression pattern is consistent with previous results from comparative microarray profiling of normal plasma cells (NPC) and MM cells. 47 Zhan and colleagues have shown that more than 90% of differentially expressed genes exhibited an increase in expression level with the transition from NPC to MGUS to MM. 47 MM cells are characterized by the overproduction of monoclonal immunoglobulins and activation of multiple growth and survival pathways.…”
Section: Discussionmentioning
confidence: 99%
“…47 Zhan and colleagues have shown that more than 90% of differentially expressed genes exhibited an increase in expression level with the transition from NPC to MGUS to MM. 47 MM cells are characterized by the overproduction of monoclonal immunoglobulins and activation of multiple growth and survival pathways. We therefore speculate that MM cells may revert their malignant phenotype by down regulation of promiscuous gene expression and by the normalization of signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from the University of Arkansas, gene expression profiling of myeloma cells using high density oligonucleotide arrays led to the identification of genes differentially expressed by tumour cells in MGUS and myeloma (Zhan et al, 2007). Unsupervised hierarchical clustering led to the identification of profiles similar to that of MGUS among patients with a clinical diagnosis of myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling has suggested that a subgroup of myeloma patients with a signature similar to that of MGUS (MGUS-like myeloma) may have a particularly good outcome after tandem HDT. (Zhan et al, 2007) It is conceivable that patients with pre-existing MGUS, SMM or PC may represent a group with more indolent disease and distinct disease biology that confers better outcome than the de novo myeloma patient undergoing HDT. We examined this question in our cohort of patients who underwent HDT for MM.…”
mentioning
confidence: 99%